Total facility management - Atkin, Brian; Brooks, Adrian (Hoboken, New Jersey Wiley Global Research, 2021)
Total Facility Management provides an accessible text bridging the gap between the theory of facility management and its practical implementation. Coverage is comprehensive, and this new edition has been written to strengthen the book's international appeal whilst retaining its relevance to the UK sector by careful alignment with recently published ISO Standards on management systems, sourcing and BIM, together with the forthcoming standards on FM strategy, user behaviour and FM organisations. In addition, alignment with British Standards on briefing (design and construction for operability) has been achieved. The book deals with many issues known to cause concern but which all practitioners should consider before embarking on a course of action. Throughout the book, the link between facilities management practice and an organisation's business objectives is emphasised.
Electronic reproduction
Keywords: Building management; Facility management; Real estate management